Titanic Voices : Memories From the Fateful Voyage - Hyslop, Donald ; Forsyth, Alastair and Jemima, Sheila (Stroud, Gloucestshire Sutton Publishing, 1994)
The RMS Titanic was supposedly unsinkable, but in the early hours of 15 April 1912 this newest flagship of the White Star Line sank with great loss of life. "Titanic Voices" relives the event through first hand accounts.
Include Bibliography and Illustration
Keywords: Shipwrecks -- North Atlantic Ocean -- Titanic (Steamship)